The Ee ja nai ka and the Meiji Restoration: A View from Nagoya through Hosono Yōsai's Kankyō manpitsu - Miura, Takashi (Journal of Religion in Japan, 2019)
Hosono Yōsai 細 野 要 斎 (1811-1878), an Owari domain official, left a voluminous diary titled Kankyō manpitsu 感興漫筆 (Random Jottings Composed at Leisure), containing accounts from 1836 to 1878. Entries addressing the late months of 1867 describe the ee ja nai ka ええじゃないかphenomenon that developed in Nagoya. Yōsai's portrayals of the ee ja nai ka contradict its received image as a rowdy pandemonium in which the populace expressed their resentment against the Tokugawa regime. Rather, what we see is a series of localized religious activities commemorating talismans (ofuda お札) that reportedly fell from the sky, many of them representing deities particularly popular in Nagoya. Based on an examination of Kankyō manpitsu, this article argues that the relationship between the ee ja nai ka and the Meiji Restoration must be evaluated on a region-specific basis and that the narrative of the Meiji Restoration is not directly relevant to understanding the nature of the ee ja nai ka in Nagoya.